Preventive Practices to Avoid Novel Coronavirus-COVID-19 at Marketplace during Lockdown in Developing Countries - Bilal Eneizan, Hussein Alhawamdeh, Kashif Arif, Alnoor Alhamzah, Odai Enaizan (International Journal of Advanced Science and Technology, 2020)
The 2019-nCoV infection that is caused by a novel type of Coronavirus resulting in severe acute respiratory syndrome (SARS-CoV-2) was first detected in China at the end of December 2019 and declared a public health emergency of international concern by the World Health Organization on January 30, 2020.Although there were many efforts to control the disease, more than 1.2 million people were infected all over the world by April 4. Social distancing and self-quarantine is a preventive measure to avoid the virus; however, the day to day needs of common people make them visit the market place somehow. Hence the critical role for shopping by the consumers in transmitting the 2019-nCoV infection from human to human, increasing in confirmed cases and death toll, cannot be ignored. Thus, the current study recommended the shoppers, especially from developing countries that“how to avoid infection from coronavirus during shopping?”. To answer this research question, six doctors were interviewed from different developing countries, and their suggestion was summarized in the result section of the paper. Keywords: COVID-19, Marketplace, Developing Countries.